2016
DOI: 10.1002/jbt.21793
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Glucose 6‐Phosphate Dehydrogenase, 6‐Phosphogluconate Dehydrogenase, and Glutathione Reductase from Rat Heart and Inhibition Effects of Furosemide, Digoxin, and Dopamine on the Enzymes Activities

Abstract: The present study was aimed to investigate characterization and purification of glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase, and glutathione reductase from rat heart and the inhibitory effect of three drugs. The purification of the enzymes was performed using 2',5'-ADP sepharose 4B affinity material. The subunit and the natural molecular weights were analyzed by SDS-PAGE and gel filtration. Biochemical characteristics such as the optimum temperature, pH, stable pH, and salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results indicated that the G6PD, 6PGD, and GR enzymes are homodimers. Similar results have been observed for rat kidney, rat lung, rat heart, trout liver, human erythrocytes, and calf liver …”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that the G6PD, 6PGD, and GR enzymes are homodimers. Similar results have been observed for rat kidney, rat lung, rat heart, trout liver, human erythrocytes, and calf liver …”
Section: Discussionsupporting
confidence: 88%
“…They found that K I values were in the range of 113.30 to 474.70 μM. Adem and Ciftci 96 purified G6PD and 6PGD enzymes from rat hearts and studied the inhibitory effects of dopamine, furosemide, and digoxin on these enzyme activities. These drugs displayed a low millimolar inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of these drug active agents that are often given for treatment on people is gaining importance. The inhibitory effects were studied on Digoxin Glucose 6-Phosphate Dehydrogenase, 6-phosphogluconate dehydrogenase and glutathione reductase enzymes [23]. Besides these, digoxin is a drug used in health care today generally for cardiac insufficiency and atrial fibrillation disorders [24].…”
Section: Resultsmentioning
confidence: 99%